The Scottish question - Mitchell, James 1960- (Oxford Univ. Press, 2014)
Over half a century ago, a leading commentator suggested that Scotland was very unusual in being a country which was a nation but in no sense a state. This title sets the Scottish independence referendum in context, exploring the questions of national identity, everyday public policy, structures of government and constitutional politics, drawing on a range of sources to illustrate why the Scottish question can never be answered definitively.
Keywords: Politische Identität; Schottland